Anti-Naegleria fowleri and Anti-Balamuthia mandrillaris Activities of Propolis - Mohammad Ridwane, Mungroo *; Ayaz, Anwar *; Siyadatpanah, Abolghsem; Norouzi, Roghayeh; Tong, Tommy *; Khan, Naveed Ahmed; Siddiqui, Ruqaiyyah (Bentham Science Publishers, 2022)
Aim: Herein, we determined the anti-amoebic properties of propolis collected from different regions in Iran against Naegleria fowleri and Balamuthia mandrillaris.